Differential Characteristics of Viral siRNAs between Leaves and Roots of Wheat Plants Naturally Infected with Wheat Yellow Mosaic Virus, a Soil-Borne Virus - Li, Linying; Andika, Ida Bagus; Xu, Yu; Zhang, Yan; Xin, Xiangqi; Hu, Lifeng; Sun, Zongtao; Hong, Gaojie; Chen, Yang; Yan, Fei; Yang, Jian; Li, Junmin; et al. (Frontiers in Microbiology, 2017)
RNA silencing is an important innate antiviral defense in plants. Soil-borne plant viruses naturally infect roots via soil-inhabiting vectors, but it is unclear how antiviral RNA silencing responds to virus infection in this particular tissue. In this study, viral small interfering RNA (siRNA) profiles from leaves and roots of wheat plants naturally infected with a soil-borne virus, Wheat yellow mosaic virus (WYMV, genus Bymovirus), were analyzed by deep sequencing. WYMV siRNAs were much more abundant in roots than leaves, which was positively correlated with the accumulation of viral RNA. WYMV siRNAs in leaves and roots were predominantly 21- and 22-nt long and equally derived from the positive- and negative-strands of the viral genome. WYMV siRNAs from leaves and roots differed in distribution pattern along the viral genome. Interestingly, compared to siRNAs from leaves (and most other reports), those from roots obviously had a lower A/U bias at the 5-terminal nucleotide. Moreover, the expression of dicer-like genes upon WYMV infection were differently regulated between leaves and roots. Our data suggest that RNA silencing in roots may operate differently than in leaves against soil-borne virus invasion.